Small-scale spatial variations of trawling impact on food web structure. (March 2019) - Preciado, Izaskun; Arroyo, Nina Larissa; González-Irusta, José Manuel; López-López, Lucía; Punzón, Antonio; Muñoz, Isabel; Serrano, Alberto
Highlights: Biomass and richness of bentho-demersal communities decline with increasing fishing effort. Fishing impact spreads through the benthic-demersal food web. Mean Trophic Level (mTL) of the community response to fishing pressure. Small-scale spatial resolution is crucial when investigating fishing impact. Abstract: Bottom trawling is one of the main anthropogenic pressures that impact soft-bottom habitats, directly affecting benthic and demersal communities, as well as their food web structure. To analyse local scale impacts of bottom trawling on food web structure we combined biological (species abundance and diets obtained from scientific bottom trawl surveys) and anthropogenic pressure (fishing effort obtained from Vessel Monitoring Systems, VMS) data. Using generalised additive models we explored the effect of bottom-trawling in nine community and trophic indicators across a gradient of fishing effort. We found an extensive effect of fishing on community indicators: with increasing fishing pressure, the biomass of seven out of fifteen functional groups declined, as well as that of the whole benthic-demersal community. Species richness was also significantly affected by bottom trawling, both at community and trophic level. We also showed a negative relationship between fishing effort and mean Trophic Level (mTL) of benthic and demersal communities at small-scale spatial resolution. Despite the apparent reduction of fishing effort observed in the study area in the last decade, we found a strong local influence of this anthropogenic pressure on the benthic-demersal food webs, demonstrating that small spatial resolution is crucial when investigating the effects of spatially heterogeneous pressures, such as fishing. Thus, we highlight the importance of analysing the effect of fishing on ecological indicators and trophic structure at local scales.